652 Association Between Poor Sleep and Lymphocyte Subsets In Chronic HIV Infection. (3rd May 2021) - Borker, Priya; Macatangay, Bernard; Punjabi, Naresh; Rinaldo, Charles; Wolinsky, Steven; Hyong-Jin Cho, Joshua; McKay, Heather; Patel, Sanjay
Abstract: Introduction: Low CD4+ T lymphocyte counts and CD4+/CD8+ lymphocyte ratios predict mortality and cardiovascular risk among people living with HIV (PLWH). Whether polysomnographic (PSG) sleep measures impact T lymphocyte subset counts among PLWH is unknown. We sought to evaluate the association between lymphocyte subsets and PSG-derived sleep measures in a cohort with HIV seropositive men. Methods: We analyzed data from HIV seropositive men who have sex with men participating in the Multicenter AIDS Cohort Study on antiretroviral therapy for >1 year with undetectable (<500 copies/mL) plasma HIV-1 RNA who underwent a sleep evaluation with home polysomnography. The following seven sleep parameters were examined: total sleep time (TST), sleep efficiency, sleep stage (N1, N2, N3, and REM) duration, and apnea-hypopnea index. Multivariable linear regression models adjusted for age and body mass index were used to assess whether sleep measures were associated with CD4+ T cell count, CD8+ T cell count, or CD4+/CD8+ ratio. Results: Participants (n= 286) had a mean age of 55.2 ± 11.3 years, 52.8% had sleep apnea and mean CD4+ count was 728 ± 306 cells/mm3. None of the sleep measures were associated with CD4+ counts but longer TST and REM duration were associated with lower CD8+ counts and higher CD4+/CD8+ ratio. In adjusted analyses, every one hour increase in TST was associated with a 35 ± 18 cells/mm3 lower CD8+ count (p=0.049) and 6.3% elevation in CD4+/CD8+ ratio (p=0.006) while every hour increase in REM was associated with 123 ± 50 cells/mm3 lower CD8+ count (p=0.01) and 20% elevation in CD4+/CD8+ ratio (p=0.003). Conclusion: In PLWH, longer total sleep time and REM sleep duration are associated with protective CD4+/CD8+ ratios due to lower CD8+ cell count. Further research is needed to assess if longer sleep duration is associated with decreased inflammatory markers. Support (if any): American Thoracic Society Academic Sleep Pulmonary Integrated Research/Clinical (ASPIRE) Fellowship